Relationship between visually estimated and calculated blood loss in primary cesarean delivery - Casquero León, Jorge Luis (2014)
Objectives: To correlate visually estimated blood loss (vEBL) with calculated estimated blood loss (cEBL) during cesarean delivery in nulliparous women. Design: correlation retrospective study. Setting: Cayetano Heredia National Hospital, Lima, Peru. Participants: Nulliparous women subjected to cesarean section. Interventions: Medical records of 160 nulliparous women atended for cesarean deliveries at term during 2011 were reviewed. Data were statically analyzed with STATA V10.1 for Windows program. Main outcome measures: Blood loss. Results: Median vEBL and cEBL were respectively 500 mL (500–600 mL) and 421.4 mL (319.85–559.65 mL) with statistical significant difference, p < 0.001. For cEBL 1 000 mL median was 1 207.80 mL (1 039.60–1 419.00 mL) and vEBL median was 500 mL (500–600 mL) with statistical significant difference, p < 0.001. Hematocrit descended 3% (3–4%). Spearman correlation coefficient between vEBL and cEBL was 0.302 (p < 0.001). Conclusions: A statistically significant weak correlation was found between vEBL and cEBL. For intrapartum bleeding less than 500 mL vEBL was overestimated and for intrapartum bleeding greater than 1 000 mL (post partum hemorrhage), vEBL was also underestimated. Visual estimation of intrapartum bleeding showed inaccurate to calculate blood loss volume. Effective alternatives methods are required that include an estimated maternal blood volume formula and changes in hematocrit. Key words: Postpartum hemorrhage, visually estimated blood loss, calculated estimated blood loss, pregnancy blood volume, primary cesarean-section.